Performance of small and medium-sized enterprises in the chemical industry in the Czech Republic: An exploratory analysis - Vojtěch Hrubý; Vojtěch Koráb (Trends Economics and Management, 2018)
Purpose of the article: The purpose of this article is to assess the performance of small and medium-sized firms in the chemical industry in the Czech Republic using a selected group of financial indicators with the aim to analyze trends, interdependencies and this segment's specifics. Methodology/methods: This study employs secondary data from the Amadeus database containing general financial information and business reports on almost 20 million European companies including those in the Czech Republic. General scientific methods such as analysis, comparison or generalization were used. Scientific aim: Only limited social science research has been done on SMEs in the chemical industry in the Czech Republic. This study aims at shedding new light on the understanding of SMEs' performance in this particular industrial segment. Findings: There is only a limited number of enterprises in the chemical industry in the Czech Republic falling into the category of SMEs, mainly because the manufacture of chemicals is a capital-intensive business. This study focuses on the financial dimension of the performance measurement with results of SMEs in this segment measurably better than the rest of the manufacturing industry. Conclusions: This paper adds to the existing research on the performance of SMEs in the Czech Republic by focusing on the chemical industry. It builds on the existing knowledge in the areas of small and medium-sized enterprises, firm performance and chemical industry in the Czech Republic by digging deep into the secondary data obtained from the Amadeus database. The analysis produced the evidence that the performance of the companies in the research sample, represented by a selected set of performance measures, is solid and better than the rest of the manufacturing industry.
Keywords: D10; M50; R10; 650; entrepreneurship; firm performance; SME; Czech Republic